U.S. - Colombia trade promotion agreement: potential economy-wide and selected sectoral effects (2006)
(TPA) on the U.S. economy as a whole and on specific industry sectors, including the effectson U.S. gross domestic product (GDP), exports and imports, employment, and consumers.Colombian exporters generally face substantially lower tariffs in the U.S. market than doU.S. exporters in the Colombian market because most U.S. imports from Colombia enter freeof duty either unconditionally or under other duty-free provisions. Because of this tariffasymmetry, the primary effects of the TPA will be improved U.S. access to the Colombianmarket and an increase in U.S. exports to Colombia. Nevertheless, the overall effect of theU.S.-Colombia TPA on the U.S. economy is likely to be small because of the small size ofthe Colombian market relative to total U.S. trade and production.The economy-wide model used by the Commission indicates that, after full implementationof the market access provisions (tariff and tariff-rate quota (TRQ) elimination) of the TPA,U.S. exports to Colombia may be higher by approximately $1.1 billion, U.S. imports fromColombia may be higher by $487 million, and U.S. GDP higher by about $2.5 billion,representing an increase of less than 0.05 percent of U.S. GDP. Only the U.S. sugar sectoris estimated to experience a decline in output, revenue, or employment of more than 0.1percent. The Commission’s findings are similar to those in other studies using similarquantitative techniques.The Commission analyzed the impact of both the immediate and the phased elimination oftariffs and TRQs of the TPA using a sector-specific analysis of selected U.S. product sectors.The sectors analyzed were meat (beef and pork); grain (wheat, rice, and corn); soybeans,soybean products, and animal feeds; chemical, rubber, and plastic products; machinery,electronics, and transportation equipment; textiles and apparel; sugar and sugar-containingproducts; and cut flowers. For most of these sectors, the TPA will provide small but positivebenefits to U.S. exports.Finally, the TPA also may increase trade and investment through trade facilitation, such asthe reduction of impediments in customs processing; improved regulatory environment, suchas enhanced investor protections; and increased regulatory transparency. The effects of suchmeasures on bilateral trade and investment flows may become more significant in themedium to long term.